Strategic management world edition - 3G E-Learning LLC, USA [author, aditor]. (New York, NY, United States of America 3G E-Learning LLC, 2023)
"This edition is completely revised and new topics are added. This comprehensive text entitled Strategic Management is a balanced coverage of both theory and practice, dealing with the essential elements of strategy making and concentrates on how the environmental context can be read to identify opportunities which will create and maintain competitive advantage." -- Preface
CHAPTER 1. STRATEGIC MANAGEMENT: AN INTRODUCTION: Introduction -- Introducing Strategy And Strategy Making -- Fundamentals of Strategic Management -- Aspects of Strategic Management.
CHAPTER 2. STRATEGY FORMULATION AND IMPLEMENTATION: Introduction -- Strategy Formulation -- Strategy Implementation -- Formulation of Functional Strategy -- Strategic Business Unit (BSU).
CHAPTER 3. STRATEGIC EVALUATION AND CONTROL: Introduction -- Strategy Evaluation Process And Its Significance -- Strategic Control Process -- Concept Of Synergy And Its Meaning.
CHAPTER 4. BUSINESS POLICY AND DECISION MAKING: Introduction -- Business Policy -- Business Policy and Its Importance -- Concept of Decision Making -- Decision Making in Management: Definition and Features.
CHAPTER 5. BUSINESS CONTINUITY PLAN: Introduction -- Concepts Of Business Continuity Plan (BCP) -- Disaster Recovery And Business Continuity -- Conclusion.
CHAPTER 6. STRATEGIC ALLIANCES: Introduction -- Concept of Strategic Alliance -- Creativity -- Business Innovation.
CHAPTER 7. BUSINESS ETHICS AND CORPORATE SOCIAL RESPONSIBILITY: Introduction -- Corporate Social Responsibility -- Business Ethics and Corporate Social Responsibility For Business Success And Growth -- Conclusion.
Includes bibliographical references and index.
Keywords: Strategic planning; Strategic management